The Portuguese crisis experience: The Triple Crunch - public, social, industrial - Mendonça, S. (From Crisis to Development: in quest of a new development model for Greece and the European South, 2014)
The nature and effects of the “Toika treatment” in Portugal is to investigated at several levels. Macro-economic level: the big picture. The public bill: the costs faced by the State. Rhe social impacts: the population under the crisis. The productive sector: the non-financial industries. Maintaining the “structural reform” rethorics is a discursive distortion: we have had policies of atriction driven by depressionary politics.